Aggregation of Stress Granules Induced by Hypoxia and Lipopolysaccharide via PKR-p-eIF2α Pathway and 4EBP1 Pathway Inhibits the Inflammatory Response in Peri-Implantitis - Li S; Ma C; Fan C; Liu Y; Li J; Yin B; Zhong L; Bai N; Li Z (Journal of Inflammation Research)
Shuang Li,1,2,* Chunling Ma,3,* Chun Fan,4 Yanshan Liu,5 Jian Li,2,6 Baoheng Yin,1,2 Lingmei Zhong,7 Na Bai,1,2 Zhiyuan Li3 1Department of Prosthodontics, The Affiliated Hospital of Qingdao University, Qingdao, Shandong, People’s Republic of China; 2School of Stomatology, Qingdao University, Qingdao, Shandong, People’s Republic of China; 3Medical Research Center, The Affiliated Hospital of Qingdao University, Qingdao, Shandong, People’s Republic of China; 4Department of Periodontology, The Affiliated Hospital of Qingdao University, Qingdao, Shandong, People’s Republic of China; 5Department of Maxillofacial Surgery, The Affiliated Hospital of Qingdao University, Qingdao, Shandong, People’s Republic of China; 6Department of Oral Implantology, The Affiliated Hospital of Qingdao University, Qingdao, Shandong, People’s Republic of China; 7Department of Pulmonary and Critical Care Medicine, The Affiliated Hospital of Qingdao University, Qingdao, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiyuan Li, Email zyli0120@163.com Na Bai, Email na.bai@qdu.edu.cnObjective: To investigate whether stress granules (SGs) exist in peri-implantitis (PI) and to explore the formation mechanism and role of SGs in the response of human gingival fibroblasts (hGFs) to hypoxia or LPS.Methods: Gingival tissues were collected from patients with PI and from healthy individuals. RT-qPCR, Western blotting, and immunofluorescence staining were used to detect the SGs in the gingiva. Healthy hGFs were cultured and the activation of SGs in LPS- or hypoxia-treated hGFs was evaluated. Knockdown assays using siRNAs were performed to investigate the formation mechanism and the role of SGs in hGFs.Results: SGs aggregates were present in gingival tissues of patients with PI. LPS or hypoxia stimulation induces SGs formation and leads to eIF2α phosphorylation and 4EBP1 hypophosphorylation in hGFs. Knockdown of PKR or 4EBP1 decreases the number of SGs in stressed hGFs and enhances LPS- and hypoxia-induced TNF-α and IL-1β expression.Conclusion: Our study revealed SGs aggregation in the PI gingiva. Hypoxia and LPS can induce SGs assembly in hGFs in vitro via PKR-p-eIF2α and 4EBP1 pathways. SGs in hGFs exert a protective effect against inflammatory responses, suggesting their role in balancing pro- and anti-inflammatory responses, thus providing a new approach for protecting against destructive inflammatory responses.Plain Language Summary: Hypoxia and Porphyromonas gingivalis-LPS induced SGs assembly in hGFs via the PKR-p-eIF2α and 4EBP1 pathways, whereas SGs exerted a protective effect against hypoxia and P. gingivalis-LPS-induced inflammatory response. Keywords: peri-implantitis, stress granules, hypoxia, LPS